2016
DOI: 10.1371/journal.pone.0153499
|View full text |Cite
|
Sign up to set email alerts
|

No Routine Postoperative Head CT following Elective Craniotomy – A Paradigm Shift?

Abstract: IntroductionPatient management following elective cranial surgery often includes routine postoperative computed tomography (CT). We analyzed whether a regime of early extubation and close neurological monitoring without routine CT is safe, and compared the rate of postoperative emergency neurosurgical intervention with published data.MethodsFour hundred ninety-two patients were prospectively analyzed; 360 had supra- and 132 had infratentorial lesions. Extubation within one hour after skin closure was aimed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…As we have previously reported, failure to extubate within 1 hour after skin closure was considered delayed extubation. 16 Surgical and anesthesia reports of all included patients and histopathological reports, where applicable, were reviewed.…”
Section: Variablesmentioning
confidence: 99%
“…As we have previously reported, failure to extubate within 1 hour after skin closure was considered delayed extubation. 16 Surgical and anesthesia reports of all included patients and histopathological reports, where applicable, were reviewed.…”
Section: Variablesmentioning
confidence: 99%
“…Schär et al (2016) 34 demonstrated in a cohort of 492 patients who had undergone elective craniotomy that routine Distribution of number of postoperative CT scans per patient. Patients received a median of 0 postoperative scans in the UMCU versus 4 in the BWH (p < 0.001).…”
mentioning
confidence: 99%
“…1 Postoperative brain CT is done routinely after cranial procedures to predict the possibility of early complications, including hemorrhage and significant brain edema. 2 Other less urgent indications are the gross assessment of the extent of resection and ventricular catheter placement in cerebrospinal fluid diversion procedures. 3 Imaging studies in our institute are done routinely for the postoperative cranial surgeries, even in the absence of clinical indication or postoperative complications; thus, raising suspicion about the role and efficacy of routine postoperative imaging.…”
mentioning
confidence: 99%